ZAKAT MANAGEMENT IN VARIOUS ERAS AND COUNTRIES, ESPECIALLY IN INDONESIA - Buditama, Izza Laveda; Niam, Siti Khozinatun (Faculty of Islamic Economics and Business, Sultan Aji Muhammad Idris State Islamic University of Samarinda, 2025)
This study explores the dynamics of zakat management across different historical periods and countries, with a specific focus on the Indonesian context. The research employs a qualitative field research approach, supported by library research methods, where various primary and secondary sources such as books and regulatory documents are utilized to enrich the analysis. The findings reveal that in several countries such as Saudi Arabia, Malaysia, Kuwait, and Sudan, the management of zakat is centrally regulated and implemented by the government. Historically, this centralized model can also be traced back to the time of the Prophet Muhammad (PBUH), followed by the caliphates of Abu Bakr (RA) and Umar ibn Khattab (RA), where the state played a dominant role in zakat collection and distribution. However, a slight shift occurred during the leadership of Uthman ibn Affan (RA) and Ali ibn Abi Talib (RA), in which the government still managed zakat but began to allow muzakki (zakat payers) to independently distribute their zakat. Indonesia today reflects this hybrid model, combining institutional zakat governance under the National Zakat Agency (BAZNAS) and private distribution by individuals. This study contributes to a deeper understanding of how religious, cultural, and political contexts influence zakat management models, highlighting Indonesia as a unique example that balances state regulation with individual autonomy.